Critical Analysis on Prescribed Guidelines of Sutika Paricharya in Ayurveda - Kajal Jha; Sah, Mithilesh Kumar; Prashant Kumar Singh (Journal of Ayurveda Campus, 2025)
Background: In Ayurveda, a woman after delivery and expulsion of the placenta is termed Sutika. The care regimen advised during this period is known as Sutika paricharya. The postnatal period, starting immediately after placental separation and lasting up to six weeks, is referred to as the puerperium. Ayurveda emphasizes maternal care during both antenatal and postnatal phases to ensure physical and psychological well-being. The objective of this review is to highlight the concept and importance of Sutika paricharya as described in Ayurvedic classics, and its role in restoring maternal health after childbirth. Materials and Methods: Classical Ayurvedic texts were reviewed to analyze Ahara (dietary regimens), Vihara (lifestyle practices), and therapeutic interventions included under Sutika paricharya. Their relevance in maintaining maternal health during the puerperal period was interpreted in the context of modern postnatal care. Results and Discussion:Ayurveda prescribes specific regimens such as swasthavritta palana (healthy daily regimen), Ahara and Vihara modifications, Garbhashaya shuddhi (uterine cleansing), Dhatu purnata (restoration of body tissues), and Stanya vriddhi (promotion of lactation). Following Sutikopacharya helps the mother regain physical strength, restore psychological balance, and return to her pre-pregnancy state, while neglect or Mithyachara (improper regimen) may predispose to chronic or difficult-to-treat disorders. Conclusion: Sutika paricharya provides a holistic framework for maternal care in the puerperal period. Its principles remain relevant for improving maternal recovery and preventing complications after childbirth. Keywords: Sutika paricharya, puerperium, postnatal care, Ayurveda, maternal health